Branched Terthiophenes in Organic Electronics: From Small Molecules to Polymers. Issue 2 (29th November 2014) - Scheuble, Martin; Goll, Miriam; Ludwigs, Sabine; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> A zoo of chemical structures is accessible when the branched unit 2, 2′:3', 2″‐terthiophene (3T) is included both in structurally well‐defined small molecules and polymer‐like architectures. The first part of this review article highlights literature on all‐thiophene based branched oligomers including dendrimers as well as combinations of 3T‐units with functional moieties for light‐harvesting systems. Motivated by the perfectly branched macromolecular dendrimers both electropolymerization as well as chemical approaches are presented as methods for the preparation of branched polythiophenes with different branching densities. Structure‐function relationships between the molecular architecture and optical and electronic properties are discussed throughout the article. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>